(untitled) - Antonio Valdes Delgado (Rome, Italy, 2001)
This book describes the sugar industry, with particular regard to the production of various categories of sugar and alcohol, processing and utilization by-products, and the manufacture of pulp and paper.
Keywords: sugar trade,sugar; manufacture and refining,by-products